The Associations of COVID-19 Induced Anxiety, Related Knowledge and Protective Behavior - Abanoub Riad; Yi Huang; Liping Zheng; Steriani Elavsky (Health Psychology Research)
On the last day of 2019, 44 pneumonia cases with unknown etiology were reported to the World Health Organization (WHO) Country Office of China. This was the first cluster of what would be defined later as coronavirus disease (COVID-19). A self-administered questionnaire with multiple-choice items was created in Microsoft Forms (Microsoft Corp. Redmond, WA. 2020). A 5-point Likert scale with ten items, where "1" refers to "Totally disagree" and "5" refers to "Totally agree," was developed to evaluate the anxiety induced by the COVID-19 outbreak highlighting the suggested sources of stress and anxious emotions, e.g., "When I or any family member go outside home during this COVID-19 outbreak I feel anxious". A 5-point Likert scale with 14 items, where "1" refers to "Not at all like me" and "5" refers to "Just like me," was developed to evaluate people's protective behaviors against coronavirus infection from 3 dimensions: Routine Protective Behaviors (RPB), Post-exposure Protective Behaviors (PPB), and Post-exposure Risky Behaviors (PRB). Items in RPB are aimed to measure individuals' protective behaviors in daily life when facing the epidemic. A multiple-choice scale of 12 items was developed to assess public awareness of COVID-19 as an emerging infectious disease. The primary objective of this work was to develop psychometrically sound scales to assess COVID-19 induced anxiety (CIAS), protective behaviors towards COVID-19 (PBCS), and COVID-19 related knowledge. The results indicated that COVID-19 induced the 6-item version of the CIAS can adequately measure anxiety level. Infectious disease outbreaks represent specific health-related crises that may impact people's emotions in different patterns according to their emerging nature. Therefore, the CIAS was designed to cover the potential anxiety sources for the general population during the COVID-19 outbreak.